Thermomechanical Impact of Polyurethane Potting on Gun Launched Electronics - A. S. Haynes; J. A. Cordes; J. Krug (Journal of Engineering)
Electronics packages in precision guided munitions are used in guidance and control units, mission computers, and fuze-safe-and-arm devices. They are subjected to high g-loads during gun launch, pyrotechnic shocks during flight, and high g-loads upon impact with hard targets. To enhance survivability, many electronics packages are potted after assembly. The purpose of the potting is to provide additional structural support and shock damping. Researchers at the US Army recently completed a series of dynamic mechanical tests on a urethane-based potting material to assess its behavior in an electronics assembly during gun launch and under varying thermal launch conditions. This paper will discuss the thermomechanical properties of the potting material as well as simulation efforts to determine the suitability of this potting compound for gun launched electronics. Simulation results will compare stresses and displacements for a simplified electronics package with and without full potting. An evaluation of the advantages and consequences of potting electronics in munitions systems will also be discussed.